2020
DOI: 10.1371/journal.pbio.3000638
|View full text |Cite
|
Sign up to set email alerts
|

Bacterially produced metabolites protect C. elegans neurons from degeneration

Abstract: Caenorhabditis elegans and its cognate bacterial diet comprise a reliable, widespread model to study diet and microbiota effects on host physiology. Nonetheless, how diet influences the rate at which neurons die remains largely unknown. A number of models have been used in C. elegans as surrogates for neurodegeneration. One of these is a C. elegans strain expressing a neurotoxic allele of the mechanosensory abnormality protein 4 (MEC-4d) degenerin/epithelial Na + (DEG/ENaC) channel, which causes the progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 70 publications
0
56
0
2
Order By: Relevance
“…Interestingly, alanine and glutamate were also shown to extend C. elegans lifespan [ 72 ]. Moreover, C. elegans ahr-1 is required for cell fate specification of GABAergic neurons [ 17 ] and it was recently shown that HT115, differently from OP50, possess the enzyme (glutamate decarboxylase, GAD) necessary to convert glutamate into GABA, which is responsible to protect C. elegans neurons from degeneration [ 74 ]. Although the authors did not check whether OP50 and HT115 indeed produce different amounts of Glu, lack of GAD is expected, consistent with our data, to increase Glu production by OP50.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, alanine and glutamate were also shown to extend C. elegans lifespan [ 72 ]. Moreover, C. elegans ahr-1 is required for cell fate specification of GABAergic neurons [ 17 ] and it was recently shown that HT115, differently from OP50, possess the enzyme (glutamate decarboxylase, GAD) necessary to convert glutamate into GABA, which is responsible to protect C. elegans neurons from degeneration [ 74 ]. Although the authors did not check whether OP50 and HT115 indeed produce different amounts of Glu, lack of GAD is expected, consistent with our data, to increase Glu production by OP50.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its responses to pathogenic bacteria, several recent studies also reveal interesting interactions between C. elegans and its commensal bacteria species. These studies show that C. elegans utilizes neurotransmitters or vitamins produced by the environmental bacteria (O'Donnell, Fox, Chao, Schroeder, & Sengupta, 2020;Urrutia et al, 2020;Wei & Ruvkun, 2020) to maintain or modulate various physiological events and neural functions. These findings together with those investigating the interactions of C. elegans and pathogenic bacteria have established C. elegans as a promising system to probe mechanisms underlying gut-brain interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In females, macrophage secretion of TNF-a and interferon-g (IFN) stimulate the development and degeneration of the corpus luteum and, in so doing; regulate ovarian function (142). In the testis, Sertoli and Leydig cells produce numerous cytokines (like TNFa, IL1, IL6, and IL18), which act as a paracrine signal that regulates germ cell development and function (143)(144)(145)(146)(147). In macrophages, IFN induces chromatin remodeling and inherited transcriptional immune memory (148), and modifications of histone marks like H4ac, H3K9ac, and H3K4me3 at IFN-activated promoters (149).…”
Section: Cytokine Signaling As a Mechanism To Influence Transgenerational Inheritance In Germ Cellsmentioning
confidence: 99%